E. coli endocarditis of the tricuspid valve. Issue 6 (2nd November 2019) - Kanwal, Arjun; Allugubelli, Navya; Kaplan, Jason; Muganlinskaya, Nargiz
ABSTRACT: Infective endocarditis (IE) is a focus of infection which effects the endocardium, specifically the heart valves or intra-cardiac devices. A 64-year-old male with gastric carcinoma and no prior cardiac history presented to the emergency room with altered mental status. Initial investigations showed the patient had a leukocytosis with a left shift. Blood cultures taken upon arrival eventually grew Esherichia coli, thought to be from the urinary tract, although initial urinalysis was delayed until after initiation of antibiotics. Electrocardiogram showed sinus bradycardia with frequent premature atrial contractions. Chest X-Ray showed bilateral pleural effusions, which were eventually drained and found to be growing E. coli . Transthoracic echocardiogram was done which showed moderate-sized tricuspid valve vegetation with severe tricuspid regurgitation. IE has been increasing in incidence throughout the years. In prior decades IE was a disease primarily affecting patients with known rheumatic heart disease, prosthetic heart valves, and intravenous drug abusers however more commonly it is becoming healthcare acquired. E. coli is not often seen to be a culprit of IE. We present a rare case of E. coli endocarditis of a native tricuspid valve.